Analysis of Performance of X21CrMoV57 and SS 410 under Simulated Conditions of Pelton Turbine with the help of Slurry Erosion Test Rig. (2018) - Mitra, Abhik; Shukla, Ashutosh; Kumar, Abhishek; Amit; Kumar, Ankit; Mittal, Rutash
Abstract: The assessment of the effects of slurry erosion under the actual operating conditions is a difficult task due to the complex nature of the influencing parameters such as velocity of flow, impingement angle, slurry concentration, properties of abrasive media, etc. However, these conditions can be simulated in a test rig by performing the abrasion of materials. Inadequate slurry flow, complex design structure, etc. are the main problems that are generally encountered during the slurry erosion testing. In the present work, a simple design of the slurry erosion test rig has been proposed which provides a better control over the slurry erosion flow and an adjustable specimen holder in comparison with the documented setups. Further, commissioning of the present test rig was carried out by determining the parameters (flow velocity, slurry concentration, and duration of testing) that influence the effect of slurry erosion on the 21CrMoV57 and SS410 metals. The metals are compared for the better performance against slurry erosion. The metals are subjected to high pressure slurry jet impingement in the test rig and analyzed with the help of SEM/EDS and XRD techniques. The observed result has shown good erosion resistant performance of 21CrMoV57 as compared to SS410.